Prevalence of multimorbidity in the Cypriot population; A cross-sectional study (2018-2019) - Kyprianidou, Maria; Panagiotakos, Demosthenes B.; Faka, Antigoni; Kambanaros, Maria; Makris, Konstantinos C.; Christophi, Costas A. (My University, 2020)
Background Multimorbidity is defined as the co-existence of two or more chronic conditions. As life expectancy is increasing so does the prevalence of multimorbidity. Our aim was to estimate the prevalence of multimorbidity in Cyprus and identify the most prevalent diseases. Methods A representative sample of n = 1140 individuals over 18 years old was surveyed during 2018–2019. Demographic characteristics as well as the presence of chronic conditions, including mental disorders, were collected through a standardized questionnaire. Diseases were classified according to the International Classification of Diseases, 10th Revision (ICD-10). Results The age and gender standardized prevalence of multimorbidity was 28.6%. Multimorbidity was associated with age (p<0.001), with the highest rate observed among people aged 65+ years old (68.9%). Multimorbidity was higher in women than men (28.2% vs. 22.5%, p < .001) but similar in urban and rural regions (26.4% vs. 23.8%, p = 0.395). The most prevalent chronic diseases among people with multimorbidity were hyperlipidemia (44.7%), followed by hypertension (37.5%), gastric reflux (23.9%), and thyroid diseases (22.2%), while the most common combinations of diseases were in the circulatory and endocrine systems. The profile of the multimorbid individual indicated this to be a person at an older age with a higher BMI, a current smoker with a higher salary. Conclusions More than one quarter of the general population of Cyprus has multimorbidity, and this rate is almost 70% among the elderly. Multimorbidity is relatively common even in younger ages too. This underlines the need for prevention strategies and health awareness programs for the entire population.
Keywords: Cyprus; Morbidity; Salaries; Physical activity; Body mass index; Hyperlipidemia; Thyroid; Age groups